Value-at-risk and stock returns: evidence from India. Issue 2 (18th April 2017) - Aziz, Tariq; Ansari, Valeed Ahmad
Abstract : Purpose: The purpose of this paper is to examine the role of value-at-risk (VaR) in the cross-section of stock returns in the Indian stock market during the period 1999-2014. Design/methodology/approach: The paper follows the methodology of Bali and Cakici (2004) to investigate the relationship between VaR and stock returns and employs Fama and French's (1993) and Fama and Macbeth's (1973) methods to find out the predictive power of VaR in time-series and cross-section settings. Further, it follows Fama and French (2008) to estimate separate cross-section regressions for small, medium and big stocks to verify the pervasiveness of the anomaly. Findings: This study finds positive risk premium associated with VaR in the Indian stock market during 2001-2008, the period of short selling constraint for institutional investors. This premium is confined to small stocks and low institutional holdings. The positive premium can be attributed to short selling constraints. Practical implications: The risk-return tradeoff can be utilized by investors and fund managers. As it is confined to small stocks, transaction costs may affect the profitability of the investment strategy. Originality/value: The study contributes to the scanty empirical literature on the role of VaR in the cross-section of expected stock returns. Moreover, this is the first study that explores the relationship between VaR and stock returns in the asset pricing context for the Indian stock market.